Analysis of p53 gene polymorphisms and protein over-expression in patients with breast cancer - (:unkn) unknown (My University, 2009)
p53 polymorphic variants play an important role in the determination of tumor phenotype and characteristics in breast cancer. In this study, we examined three common polymorphisms in p53 gene and their haplotype combinations to assess their potential association with inherited predisposition to breast cancer development, in relations with the protein over-expression and patients' demographic data. A total of 99 patients with breast cancer and 107 age-matched healthy controls were included in the study. Genotypes were determined using PCR-RFLP and DNA sequencing techniques. Evaluation of p53 protein over-expression was also examined by immunohistochemistry. Among three polymorphisms, increased codon 72 Pro allele frequency (p = 0.0067) and the presence of Pro allele were found to be significantly associated with breast cancer (p = 0.013). A significant risk was also found in subjects with combinations of specific haplotypes and genotypes. Most of breast cancer women especially younger than 50 years carry at least one p53 polymorphism (p = 0.001). There was no any association between these three p53 polymorphisms and the protein over-expression, separately or in interaction, with breast cancer. In conclusion, presence of proline allele at codon 72 alone, and its special combinations with other two polymorphisms appear to be a significant risk factor for breast cancer. Determination of well-known p53 polymorphisms might be a good predictor for breast cancer development especially in women younger than 50 years.
Keywords: Adult; Female; Humans; Middle Aged; Biomarkers, Tumor; Immunohistochemistry; Genotype; Polymorphism, Single Nucleotide; Risk Factors; Genetic Predisposition to Disease; Polymerase Chain Reaction; Breast Neoplasms; Polymorphism, Restriction Fragment Length; Base Sequence; Tumor Suppressor Protein p53